URBANIZATION AND BIODIVERSITY: THE NATURALIZATION OF URBAN DEVELOPMENT. - Solijonova Raykhona (TADQIQOTLAR, 2025)
Abstract:  Today  a  large  part  of  the  world's  population  lives  in  cities.  The process of urbanization continues at a rapid pace, and this process affects all aspects of human life. Cities are expanding, new infrastructures are being built, economic and cultural life is developing. However, not only does urbanization remain associated with human  activities,  it  also  has  a  significant  impact  on  the  natural  environment  and biodiversity.  The  naturalization  of  urban  development  is  understood  as  the harmonization of the urbanization process with nature, actions aimed at preserving and developing  biodiversity.  This  article  discusses  the  impact  of  urbanization  on biodiversity, the integration of cities with the natural environment, the development of urban ecosystems and the challenges and prospects in this process.